A expansão do agronegócio e o desenvolvimento socioeconômico de municípios da nova fronteira agrícola (Matopiba): uma análise de 2000 e 2010 - Jesus, Francisdalva Rosa de (2023)
The growth of Brazilian agricultural production identified a great structural dynamism, considering the opening of the internal market through industrial production, of the aggregation of new areas, previously isolated, and the integrated production to the national economy. However, there are studies showing that the results are not characterized in better living conditions of the population. This study is structured in two chapters that address the expansion of agribusiness in the municipalities of the new agricultural frontier (MATOPIBA) and more specifically in the state of Piauí. In the first chapter, we sought to identify and analyze the socioeconomic development, based on the expansion of agribusiness, in the municipalities of the new agricultural frontier (MATOPIBA) in the years 2000 and 2010, and in the second chapter, we analyzed the evolution of socioeconomic development, based on the expansion of agribusiness, in the state of Piauí, with emphasis on the municipalities in the region of Cerrado Piauiense, during the period 2000 and 2010. To consolidate the analysis, in addition to bibliographical and documental research, Factor Analysis (FA) was used in the two chapters, to develop the construction of a socioeconomic development index that encourages understanding the degree of socioeconomic development of the municipalities that are part of the new agricultural frontier, MATOPIBA and the state of Piauí. The AF model had a satisfactory adequacy and pointed to the existence of sufficient correlations between the variables to proceed with it, through Bartlett's and KMO's sphericity tests. With a total explained variance greater than 0.70 of the total variance of the 15 chosen variables. In the extraction of the factors, 04 constructs were used to construct the Socioeconomic Development Index and enabled a classification into three degrees of development (low, medium and high) among the municipalities used in the study. The results showed, in both chapters, that the classification ranking and the values of the Socioeconomic Development Index are discrepant and expose the heterogeneity in the municipalities that make up the new agricultural frontier (MATOPIBA), as well as in the state of Piauí. Evidences highlight the need to elaborate a public policy aimed at promoting territorial development, which should consider relevant aspects, such as education, health, inequality, basic sanitation, among others.